2018
DOI: 10.1152/ajpregu.00291.2017
|View full text |Cite
|
Sign up to set email alerts
|

Venous collapse regulates intracranial pressure in upright body positions

Abstract: Recent interest in intracranial pressure (ICP) in the upright posture has revealed that the mechanisms regulating postural changes in ICP are not fully understood. We have suggested an explanatory model where the postural changes in ICP depend on well-established hydrostatic effects in the venous system and where these effects are interrupted by collapse of the internal jugular veins (IJVs) in more upright positions. The aim of this study was to investigate this relationship by simultaneous invasive measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 33 publications
3
55
3
2
Order By: Relevance
“…Of note, venous pressure has been shown by Holmlund et al to be predictive of changes in intracranial pressure with increases in venous CSA correlating with increases in intracranial pressure [25]. Moreover, Holmlund et al also showed increases in venous CSA as well as central venous pressure as tilt angle increased from sitting to supine which is again consistent with our results [25].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Of note, venous pressure has been shown by Holmlund et al to be predictive of changes in intracranial pressure with increases in venous CSA correlating with increases in intracranial pressure [25]. Moreover, Holmlund et al also showed increases in venous CSA as well as central venous pressure as tilt angle increased from sitting to supine which is again consistent with our results [25].…”
Section: Discussionsupporting
confidence: 91%
“…Of note, venous pressure has been shown by Holmlund et al to be predictive of changes in intracranial pressure with increases in venous CSA correlating with increases in intracranial pressure [25]. Moreover, Holmlund et al also showed increases in venous CSA as well as central venous pressure as tilt angle increased from sitting to supine which is again consistent with our results [25]. These ndings are, however, tempered by one study that showed that measured ICP and central venous pressure both decreased during acute (<1 minute) episodes of zero G in parabolic ight, which differs from ndings of increased central venous pressure during HDT [26].…”
Section: Discussionmentioning
confidence: 94%
“…The significant dilation of the jugular vein, which we observed during head-down tilts (Figure 10B), is a frequent finding during venous pooling in the head [46,47]. Orthostatic gradients associated with head-up posture frequently induce the collapse of the jugular vein [5,48]; in contrast, head-up rotations in the alligator produced variable changes in the jugular luminal area, including increases in luminal area. One cause of the largerthan-expected jugular luminal areas during head-up rotations may be the unusual patterns of heart rate observed during thisstudy (see below), but it may also reflect the nature of the cephalic venous system in alligators.…”
Section: Discussionmentioning
confidence: 70%
“…, where p CVP−p d represents the pressure difference between CVP and dural sinus pressure due to venous flow and flow resistance. Holmlund et al [61] reported CVP in healthy controls in supine position to be 4.2 mmHg. Avasthey [62] measured venous pressure at various sites in the venous system and found a pressure increase of approximately 2.2 mmHg from the CVP (measured in the right atrium) to the internal jugular vein at the level of the ear.…”
Section: Resistance and Pressure For Outflow Into Dural Sinus Or Lympmentioning
confidence: 99%
“…Adding the pressure increases from the right atrium to the sagittal sinus we can approximate p CVP−p d = 4.2 mmHg and p d = 8.4 mmHg . It should be noted that both ICP and the dural venous pressure changes with body position [61], and that we only considered the supine position.…”
Section: Resistance and Pressure For Outflow Into Dural Sinus Or Lympmentioning
confidence: 99%